395 UNDERSTANDING RESIDENT CONCERNS WITH AMBULATORY CARE EXPERIENCES IN TRAINING. Issue 1 (1st January 2007) - Powell, C.; Brownfield, E.
Abstract : Purpose: Internal medicine residents have been increasingly choosing subspecialty careers over those in general internal medicine. Resident evaluations of the ambulatory general internal medicine training have been consistently decreasing. Ambulatory internal medicine has become complicated across all practice settings, academic to private practice. The office microsystem has become a target for meaningful primary care change. We conducted resident focus groups to discuss ambulatory experiences during training. Methods: All residents were invited to participate in one of three focus groups over the standard noon conference time. Thirty-nine (43%) residents participated. Three sessions were held, one for each level of training: postgraduate year (PGY) 1, 2, and 3 or higher, with similar numbers participating in each session. Resident comments were elicited on the topics of dislikes with the ambulatory experience, educational benefit of both continuity clinic and ambulatory care block experiences, types of patients cared for in the clinic, learning needs, and the ideal resident clinic. Results: The primary themes that emerged from the focus groups included patient scheduling, medical records, clinic organization, system-based care, patient characteristics, resident expectations of attendings and vice versa, and resident education, including didactics, evaluation, and areas in which residents lack confidence due to lack of sufficient exposure. These limited-exposure areas included prevention, office procedures, dermatology, sports medicine/orthopedics, business of medicine and billing, time management, and researching clinical questions in an office setting. Overall, these themes and concerns were consistent across all levels of training. Conclusions: Internal medicine residents have traditionally felt that residency culture is inpatient-centric and therefore voiced concerns spanning all areas of their ambulatory education. The resultant themes from our focus groups parallel those concerns plaguing most internal medicine practices, academic to private practice. With this knowledge, ambulatory education can change to meet residents perceived needs, improve confidence with general internal medicine knowledge and skills, and potentially result in higher percentages of residents choosing a career in general internal medicine. We are tailoring the ambulatory experiences in our residency program to include changes based on our residents' concerns.